Willingness to Pay for Police Reform - Powell, Zachary A. (Criminal justice policy review, 2021)
Consent decrees, authorized by Section 14141 of the 1994 Violent Crime Control Act, represent one of the most powerful governmental tools used to encourage—and possibly force—police reform. The consent decree process, however, carries a significant fiscal burden; in some cases, the cost of police reform inhibits agencies’ cooperation with the decrees. One possible solution to this problem calls for the creation of a public-supported police reform fund, whose monies are reserved strictly for consent decrees. Guided by focal concerns theory, this study reports on a factorial survey experiment used to assess variation across individuals’ willingness to pay for police reform. Results indicate that the seriousness of a police reform issue and the agency’s ability to pay for reform act as significant drivers of endorsement of a police reform fund.